2018
DOI: 10.13080/z-a.2018.105.028
|View full text |Cite
|
Sign up to set email alerts
|

Changes in weed seed bank and flora as affected by soil tillage systems

Abstract: Tillage not only changes soil properties but also serves as a weed control means. Different soil tillage systems were investigated in a long-term field experiment conducted during 2003-2012 at Institute of Agriculture, Lithuanian Research Centre for Agriculture and Forestry. The experiment was carried out in a cereal-based crop rotation. The experimental design included the following tillage treatments: 1) conventional tillage (CT): mouldboard ploughing at 22-24 cm depth; 2) minimum tillage (MT): stubble culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
(30 reference statements)
2
14
0
Order By: Relevance
“…The lowest (16.7-19.3%) seed number was found at a soil depth of 20-30 cm. Soil contamination with weed seeds depended on crop condition as well as application of agromeasures and corresponds to consistent patterns indicated in literature (Woźniak, Soroka, 2015;Auškalnienė et al, 2018;Skuodienė et al, 2018). The seed bank is an indicator of past and present weed populations.…”
Section: Weed Species Diversity In the Crops Of The Rotation During Tsupporting
confidence: 86%
See 1 more Smart Citation
“…The lowest (16.7-19.3%) seed number was found at a soil depth of 20-30 cm. Soil contamination with weed seeds depended on crop condition as well as application of agromeasures and corresponds to consistent patterns indicated in literature (Woźniak, Soroka, 2015;Auškalnienė et al, 2018;Skuodienė et al, 2018). The seed bank is an indicator of past and present weed populations.…”
Section: Weed Species Diversity In the Crops Of The Rotation During Tsupporting
confidence: 86%
“…In high productivity Cambisol with pH 6.9-7.0, significant differences in the weed species composition between the different tillage systems were recorded: no tillage system promoted infestation of some broadleaf weeds, particularly shepherd's purse (Capsella bursapastoris (L.) Med.). The lowest weed mass was determined for the conventional tillage plots compared to minimum tillage, and especially for no tillage plots (Auškalnienė et al, 2018). In low productivity Retisol with pH 5.1-5.3, primary soil tillage method had significant impact on the weediness of crop rotation in all experimental years.…”
Section: Weed Species Diversity In the Crops Of The Rotation During Tmentioning
confidence: 88%
“…From a longterm experiment, one year overview showed that soil tillage and level of fertilizer application influenced weed fresh biomass and, because of high propagation level of perennial species, weed fresh biomass was the highest under no-tillage (149.6 g m -2 ) even without fertilizers application ( Fig.). Results of regression analysis pointed out that weed fresh biomass decreased when intensity of soil tillage increased from no-tillage to conventional tillage (Auškalnienė et al, 2018). On the other hand, weed fresh biomass was negatively correlated (R = −0.66) with maize yield in unfavourable and dry years (Simić, Dolijanović, 2016).…”
Section: Temperature Precipitationmentioning
confidence: 99%
“…The interest in reduced (non-inversion) soil tillage in Lithuania has emerged over the last decades as well. It was established that shallow ploughing and rototilling did not exert any negative effect on soil agrochemical and physical properties (Feiza et al, 2011), and shallow tillage can give similar yields to mouldboard ploughing (Arvidsson et al, 2014), nonetheless the amount of seeds in the soil, as well as weed mass was significantly higher in less disturbed systems particularly in reduced-tillage system (Auškalnienė et al, 2018;Kadziene et al, 2020).…”
Section: Introductionmentioning
confidence: 99%